Do individual factors affect the relationship between faculty intrapreneurship and the entrepreneurial orientation of their organizations? - Ahmed Bani-Mustafa; Sam Toglaw; Oualid Abidi; Khalil Nimer (Economies, 2021)
Several colleges and universities in the Middle East have been undertaking significant initiatives to forge and foster corporate entrepreneurship. The viability and success of those initiatives rest upon the input of faculty, possessing to various degrees an entrepreneurial orientation that revolves around innovativeness, risk-taking, and proactivity. This study investigates the extent to which individual-level factors moderate the influence of faculty entrepreneurial behavior on the entrepreneurial orientation of higher education institutions in Kuwait. These factors include gender, academic qualifications, teaching experience, school affiliation, scientific productivity, industrial experience, and professional certification. Data were collected using questionnaires filled by 291 faculty members, and the model was analyzed using structural equation modelling. The differences for each faculty characteristic in the structural path coefficients were tested using the Z-score statistics. The eight hypotheses that were partially validated as the most notable findings indicate that entrepreneurial orientation among male or business faculty has a greater impact on their institutions' organizational, entrepreneurial orientation. In contrast, the differences for the rest of the moderating characteristics were insignificant. The originality of this study pertains to the fact that the scope of faculty intrapreneurship does not seem to be strongly affected by any individual-level characteristic.
Keywords: 330; entrepreneurial orientation; faculty characteristics; faculty intrapreneurship; structural equation modelling